Promoting students as partners in a pilot study involving undergraduate students and instructors in Spanish as a foreign language courses - García-Allén, Ana; Heru, Sari; Martínez, Richard (International Journal for Students as Partners, 2024)
Through the student-as-partners (SaP) framework, this paper explores how this can enhance undergraduate Spanish as a foreign language flipped classroom courses and promote student engagement and satisfaction. Traditionally, higher education courses are designed and developed by faculty members; however, our pilot project proposed collaboration between students and instructors in the design and implementation of course activities. This paper explores the model’s effects and outcomes through four surveys administered at the end of the academic year. Each survey included key factors related to the learning experience: student enjoyment, emotional support, relatedness to peers, feedback from/for students, and content-related support. Collectively, these perspectives were used to reflect on the feedback provided, which helped us achieve our objective: the creation of teaching and learning resources to engage future cohorts and increase student retention. Although this model is presented in the foreign language context, it is transferable to any discipline.